2010
DOI: 10.1098/rsta.2010.0054
|View full text |Cite
|
Sign up to set email alerts
|

Climate forcing of volcano lateral collapse: evidence from Mount Etna, Sicily

Abstract: In this study, we present evidence for early Holocene climatic conditions providing circumstances favourable to major lateral collapse at Mount Etna, Sicily. The volcano's most notable topographic feature is the Valle del Bove, a 5 × 8 km cliff-bounded amphitheatre excavated from the eastern flank of the volcano. Its origin due to prehistoric lateral collapse is corroborated by stürtzstrom deposits adjacent to the amphitheatre's downslope outlet, but the age, nature and cause of amphitheatre excavation remain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 53 publications
2
10
0
Order By: Relevance
“…Preconditioning factors may include: (1) high sedimentation rates; (2) water saturation due to rising sea level; (3) elevated pore‐fluid pressures; (4) high rainfall; (5) hydrothermal alteration; (6) deep narrow canyons reducing lateral strength; (7) faulting; (8) dyke intrusion; (9) seismic activity; (10) volcanic spreading; and (11) residual soils [ Siebert ; Siebert et al ., ; McGuire et al ., ; Elsworth and Voight , 1995, 1996, ; Murray and Voight , ; Day , ; McGuire , ; Voight and Elsworth , ; Hürlimann et al ., ; Masson et al ., ]. Recent studies have suggested a relationship between increased erosion and runoff, associated with the onset of warmer interglacial intervals, as a potentially important preconditioning factor [ McGuire , ; Keating and McGuire , ; McMurtry et al ., ; Deeming et al ., ; Tappin , ; Hunt et al ., ]. However, there are few field data sets suitable for testing rigorously these competing models for preconditioning factors and triggers.…”
Section: Introductionmentioning
confidence: 99%
“…Preconditioning factors may include: (1) high sedimentation rates; (2) water saturation due to rising sea level; (3) elevated pore‐fluid pressures; (4) high rainfall; (5) hydrothermal alteration; (6) deep narrow canyons reducing lateral strength; (7) faulting; (8) dyke intrusion; (9) seismic activity; (10) volcanic spreading; and (11) residual soils [ Siebert ; Siebert et al ., ; McGuire et al ., ; Elsworth and Voight , 1995, 1996, ; Murray and Voight , ; Day , ; McGuire , ; Voight and Elsworth , ; Hürlimann et al ., ; Masson et al ., ]. Recent studies have suggested a relationship between increased erosion and runoff, associated with the onset of warmer interglacial intervals, as a potentially important preconditioning factor [ McGuire , ; Keating and McGuire , ; McMurtry et al ., ; Deeming et al ., ; Tappin , ; Hunt et al ., ]. However, there are few field data sets suitable for testing rigorously these competing models for preconditioning factors and triggers.…”
Section: Introductionmentioning
confidence: 99%
“…Profile 4 A(II) 32(2) 20(1) 8(1) 2(0) -18(3) 5(1) 3(0) 4(1) 3(1) 4(0) 1(0) 2Ab(IV) 22(2) 9(1) 1(0) 12(2) 1(0) 21(2) 12(1) 3(1) 5(2) 6(0) 7(1) 1(0) 2Bwb(IV) 14(1) 21(2) 5(1) 28(2) 4(1) 11(1) 4(1) 2(0) 2(1) 3(1) 6(1) - trace minerals in the eruptions of the volcanoes forming the Campanian (Neapolitan) volcanic complex (Carati, 1988;Rosi and Sbrana, 1987;Russo and Punzo, 2004;Scheibner et al, 2008) while these minerals are known to be rare in the Etnean volcanic products (Deeming et al, 2010) and present as traces into products erupted not earlier than 4000 YBP (Kamenetsky et al, 2007). Subsequently, during glacier recession, tephra was redeposited as part of the active outwash of material into the neo-formed kettle holes.…”
Section: Cannella Valley Majella Massifmentioning
confidence: 97%
“…Rapid ice-mass loss at the many glaciated volcanoes in Alaska and Kamchatka, driven by surface temperature rises that could exceed 15 • C by 2100 (Sanderson et al submitted), has the potential to promote eruptions, either as a consequence of reduced load pressures on magma reservoirs or through increased opportunity for magma-water interaction. Additionally, the potential for edifice lateral collapse could be enhanced as a consequence of elevated pore-water pressures arising from meltwater and a significant predicted rise in precipitation (Capra 2006;Deeming et al 2010). The potential for both volcanic and non-volcanic landslides may also be promoted by increased availability of water leading to slope destabilization and failure due to slow cracking, held to be a contributory factor in the formation of stürtzstroms (giant, rapidly moving, landslides) (e.g.…”
Section: Climate Forcing Of Hazards In the Geospherementioning
confidence: 99%
“…Additionally, the potential for edifice lateral collapse could be enhanced as a consequence of elevated pore-water pressures arising from meltwater and a significant predicted rise in precipitation (Capra 2006;Deeming et al 2010). The potential for both volcanic and non-volcanic landslides may also be promoted by increased availability of water leading to slope destabilization and failure due to slow cracking, held to be a contributory factor in the formation of stürtzstroms (giant, rapidly moving, landslides) (e.g.…”
Section: (A) High-latitude Regionsmentioning
confidence: 99%